2019
DOI: 10.1002/cbic.201900300
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Substitution Registry on the Receptor‐Activation Profiles of Backbone‐Modified Glucagon‐like Peptide‐1 Analogues

Abstract: Family BGprotein-coupled receptors play importantp hysiological roles and possess large extracellular domains (ECDs) that aid in binding the long polypeptide hormones that are their natural agonists. We have previously shown that agonist analogues in which subsets of native a-amino acid residues are replaced with b-aminoa cid residues can retain activity while avoiding proteolytic degradation. This study focuses on eight new a/b analogues of glucagon-like peptide 1( GLP-1) that each contain five a-to-b replace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…29 We previously showed that GLP-1 analogues with multiple (S,S)-ACPC substitutions in the C-terminal region, which is α-helical when bound to the ECD, 30 display substantial agonist activity. 31,32 In contrast, (R,R)-ACPC (Fig. 1a) destabilizes a right-handed α-helix-like conformation by >1 kcal/mol relative to (S,S)-ACPC or L-Ala. 29 As observed for D-Ala, 24 (R,R)-ACPC can replace Gly to stabilize turn segments.…”
Section: Resultsmentioning
confidence: 97%
“…29 We previously showed that GLP-1 analogues with multiple (S,S)-ACPC substitutions in the C-terminal region, which is α-helical when bound to the ECD, 30 display substantial agonist activity. 31,32 In contrast, (R,R)-ACPC (Fig. 1a) destabilizes a right-handed α-helix-like conformation by >1 kcal/mol relative to (S,S)-ACPC or L-Ala. 29 As observed for D-Ala, 24 (R,R)-ACPC can replace Gly to stabilize turn segments.…”
Section: Resultsmentioning
confidence: 97%
“…52 We previously showed that GLP-1 analogues with multiple ( S , S )-ACPC substitutions in the C-terminal region, which is α-helical when bound to the ECD, display substantial agonist activity. 53,54 In contrast, ( R,R )-ACPC (Fig. 1a) destabilizes a right-handed α-helix-like conformation by >1 kcal/mol relative to ( S,S )-ACPC or L-Ala. 52 As observed for D-Ala, 55 ( R , R )-ACPC can replace Gly to stabilize turn segments.…”
Section: Resultsmentioning
confidence: 97%
“…The cells we used overexpress the Glosensor, , which allowed us to determine whether the Flag tag influences GIPR signal transduction as mediated by intracellular cAMP production. We chose HEK293 cells because this cell line is commonly used in pharmacological studies involving family B GPCRs. Furthermore, HEK293 cells endogenously express GRK isoforms 2, 3, 4, 5, and 6; GRK2 and GRK5 have previously been shown to regulate GIPR internalization. , …”
Section: Resultsmentioning
confidence: 99%